Posterior Segment Pathologies in Patients with Ocular Trauma Using B-Scan Ultrasonography: http://doi.org/10.36351/pjo.v37i2.1197 - Tanweer, Fatima Sidra; Rana, Afia Matloob; Akhter, Waseem (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the frequency of posterior segment pathologies caused by ocular trauma using B scan USG. Study Design: Descriptive, cross-sectional study. Place and Duration of Study: Holy family hospital, Rawalpindi, from September 2015 to March 2016. Methods: One hundred patients of ocular trauma, 12 to 45 years of age were included in the study. Patients who had any posterior segment pathology prior to the ocular trauma were excluded. B scan was performed in all patients. The data was collected and analyzed using SPSS version 17. For all the categorical variables like gender, type and site of ocular injury, the side of eye involved, type of posterior segment pathology as detected on B Scan, frequencies and percentages were calculated. For the continuous variables like age and time since injury, mean and standard deviation were calculated. Results: Mean age was30.43 ± 9.58 years. Majority of the patients (35.0%) were between 26 to 35 years of age. Out of these 100 patients, 73 were males and 27 were females with male to female ratio of 2.7:1. Vitreous hemorrhage was the most common and ocular pathology (38 patients). Retinal detachment was seen in 21 patients. Intra-ocular foreign bodies were seen in 12 patients. Conclusion: Vitreous hemorrhage was the most common posterior segment pathology in ocular trauma followed by retinal detachment and intra-ocular foreign bodies. Key Words: Trauma, B-scan, Vitreous hemorrhage, Retinal detachment.